HOMOSEXUAL TENDENCY OF CHARACTER ‘’I’’ IN TENNESSEE WILLIAM’S MOISE AND THE WORLD OF REASON (Universitas Islam Negeri Sunan Ampel Surabaya, 2013)
Moise and the World of Reason is one of William’s novels. It was published in 1975. This novel tells about character ‘’I’’ who is identified as a homosexual (a person who is involved in sexual desire with the same sex). There are some factors in supporting this tendency. The first is social background. It consists of the family background where he grew up. He was separated from his parents. Then, he had experiences when he was young. The second factor is his relation to the other men characters. The aim of this analysis is to know how Tennessee Williams describes character ‘I’ and his experiences in Moise and the World of Reason.Keywords: homosexual, tendency and character.